A Rapid Molecular Detection System for Sdh Mutations Conferring Differential Succinate Dehydrogenase Inhibitor Resistance in Corynespora cassiicola - Sun, Bingxue (Plant disease, 2023)
Cucumber leaf spot, caused by Corynespora cassiicola, is a serious disease of cucumbers in greenhouses. Due to the frequent application of succinate dehydrogenase inhibitors (SDHIs), resistance caused by point mutations in the SDHB/C/D gene has been reported. Different mutations lead to different resistance levels, and mutations vary over time and regions. This means that it is necessary to know the type of mutation in the field to select the appropriate SDHIs. Here, the sensitivity of mutations to SDHIs was determined, and eight resistance patterns were obtained: pattern I (BosVHR, FluoMR, PenHR, CarR); pattern II (BosMR, FluoSS, PenS, CarS); pattern III (BosVHR, FluoSS, PenLR, CarS); pattern IV (BosLR, FluoLR, PenS, CarR); pattern V (BosMR, FluoLR, PenS, CarS); pattern VI (BosMR, FluoLR, PenLR, CarS); pattern VII (BosVHR, FluoHR, PenHR, CarS); and pattern VIII (BosLR, FluoLR, PenLR, CarS). We successfully established nine allele-specific PCR (AS-PCR) assays that can detect mutation types. The sensitivity and specificity of AS-PCR were also determined. The sensitivity results showed that most of the detection thresholds of the AS-PCR assays were 100 pg/μl, while the AS-PCR assay of the B-H278R and D-G109V mutations exhibited high sensitivity, with 10 pg/μl. To validate the use of the developed AS-PCR assay, DNA from leaves inoculated with known mutations was extracted, detected by AS-PCR, and sequenced. The results showed good similarity between the two methods. Additionally, to rapidly detect mutations in the CcSdhD gene, we developed a single-tube multiplex allele-specific PCR (MAS-PCR) assay. In conclusion, AS-PCR and MAS-PCR were established for mutation detection and targeted control of CLS